Pelatihan Penyusunan Laporan Keuangan pada BUMDes Desa Balesari - Kartika Pradana Suryatimur; Siti Afidatul Khotijah; Panji Kusuma Prasetyanto (Jurnal Pengabdian UntukMu NegeRI, 2020)
This community service program aims to provide an understanding of financial reports to BUMDes administrators. This program is implemented for BUMDes management in Balesari Village, Windusari District, Magelang Regency, Central Java Province. The service method used is training and discussion. The result of this activity is that BUMDes administrators can understand and prepare financial reports well. Previously, BUMDes management only recorded cash disbursements and income, did not classify transactions that occurred, so that the financial reports could not provide appropriate financial information. By having a basic understanding of accounting, BUMDes management can classify each transaction and record it according to the account, so that BUMDes' financial reports are tidier and can provide good information to their users.